S-Nitrosation impairs activity of stress-inducible aldehyde dehydrogenases from Arabidopsis thaliana - Stiti, Naïm (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2019 Elsevier B.V. All rights reserved.